Exploring Corrosion Laboratory Activities in Supporting Electrochemistry Analytical Competence among Pre-service Science Teachers - Soraya Firdausi; Sri Rejeki Dwi Astuti; Ferry Budi Prasetya; Eka Puspita Kartika Sari; Jadnika Dwi Rahmawan Amrullah; Rhischa Assabet Shilla (Universitas Syiah Kuala, in collaboration with the Perkumpulan Pendidik IPA Indonesia (PPII), (MoU), 2026)
Difficulties in understanding electrochemistry concepts remain a persistent challenge among pre-service science teachers. Laboratory activities are often used to help students connect theoretical knowledge with observable phenomena. This study aimed to examine the relationship between performance assessment in corrosion laboratory activities and analytical competence in understanding electrochemistry theory among pre-service science teachers. The research involved 121 pre-service science teachers enrolled in a second-year general chemistry course. Data were collected through performance assessment during corrosion laboratory activities and analytical competence tests related to electrochemical concepts. Descriptive statistics and normality tests were conducted prior to the correlation analysis. Since the data were not normally distributed, the relationship between the variables was analyzed using Spearman’s rho correlation. The results revealed a positive and statistically significant relationship between performance assessment and analytical competence (ρ = 0.254, p < 0.05). However, the strength of the relationship was weak. Regression analysis further showed that performance assessment accounted for 3.9% of the variance in analytical competence (R² = 0.039). These findings indicate that while laboratory performance is associated with students’ analytical competence in understanding electrochemistry theory, its contribution remains limited